Implikatur yang Menimbulkan Humor dalam Serial Rokunin no Okusan oleh Shimura Ken - Muhaimin Muhaimin (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2020)
The purpose of this study was to describe the implicature of conversation that arise as the result of the violation of Grice’s cooperative principle. The result showed that the implicature of conversation that exist in those speeches had been preeceded by violation of 4 maxims. There are implicature of conversation which are; apology, threat, denial, sneer, order, rebuke, emphasize, change of subject, intimidate, influence, and rejection. Based on the violation cooperative principle, the were conversational implicature which gave humor effects. Implicature of conversation which gave humor effects to the audience are : (1) Implicature which is a representation of an unexpected situation or something contrary. (2) Implicature which has potential, soften, mistreat, bother, cornered the speaker or spoken partner. (3) Implicature whis is a representation of unwanted condition, rejection, disagreement, compulsion, anger, and resistance. Implicature used as a medium of humor from the speaker to the audience signed by laughter of the audience, so that the purpose of humor program could be delivered which is to entertain people.